THE INFLUENCEâS FACTORS IN CHOOSING DEPO MEDROXY PROGESTERONE ACETATE (DMPA) INJECTION CONTRACEPTION IN BPM KANTIN SUSILOWATI Amd.Keb - Khusniyati, Etik; Rahmawati, Ima (JURNAL KEPERAWATAN SEHAT, 2015)
According to Indonesian Public Health, Keluarga Berencana (KB), made by Indonesia government, not only to control birth rate but also to decrease mortality rate of mother and baby. The election of family planning program, injection contraception DMPA is widely used by woman compared to other contraception. The purpose of this research is to know the factors which influence the using Depo Medroxy Progesterone Acetate (DMPA) injection contraception in BPM Kantin Susilowati Amd.Keb. This research use descriptive research as method and the instrument use questionnaire. From the population of this research which is 69 mothers using DMPA injection contraception, the sample has taken by purposive sampling is 40 respondents. The research instrument in the form of a questionnaire. Data analysis used is frequency distribution table. The result of the research is the researcher has found several dominant reasons or factors influence in choosing DMPA injection contraception in BPM Kantin Susilowati Amd.Keb,, couple relationship“communication before choosing birth control method”40 respondent (100%), PMS risk“doesn’t have risk” 40 respondent (100%), HIV infection and the use of contraception“doesnât have HIV infection” 40 respondent (100%), religion believe and culture“It is permitted using injection contraception”40 respondent (100%), and women status“has their own authority in decision taking”40 respondent (100%). Public health influence in the selection of the injection contraception DMPA doesn’t have PMS risk and HIV infection, the person can choose any contracetion, and injection contraception DMPA they choose to look at the effectiveness of high and profitsnhave injection contraception DMPA.Key Word : Factors, DMPA Injection Contraception.